Cloning and Expression Characteristics of BhARF4 Gene in Wax Gourd (Benincasa hispida) - Xiaoxin CHENG; Xuling ZHAI; Jinqiang YAN; Baochen WANG; Renliang MO; Wenrui LIU; Zhiming WU; Biao JIANG (Guangdong nongye kexue)
【Objective】The ARF4 gene of wax gourd (Benincasa hispida) was cloned and its expression patterns in different tissues were studied by bioinformatics analysis, thereby providing a reference for further exploration of the function of BhARF4 in the development of wax gourd fruits.【Method】With the cDNA of the fruits of B227 on the day of flowering as template, specific cloning primers were designed according to the CDS sequence of BhARF4 in the reference gene. At the fruiting stage, samples of B227 were taken from different tissues (root, stem, leaf, female and male flowers on the day of flowering, as well as fruits on different days after pollination (DAP) (0, 5, 10, 15, 20 and 30 DAP). The expression patterns of BhARF4 in different tissues of fruits were analyzed by qRT-PCR.【Result】The BhARF4 gene contained 12 exons and 2 introns, with its CDS sequence length of 2 412 bp. Motif and conserved domain analysis revealed that the BhARF4 protein contained 9 motifs and conserved ARF, AUX_IAA, and B3 domains. The phylogenetic analysis revealed that the BhARF4 protein exhibited the highest degree of similarity to the ARF4 protein derived from cucumber and melon, while displaying the most distant relationship to those from Arabidopsis thaliana and Cucurbita moschata. The gene expression pattern analysis revealed that the expression of ARF4 was highest in melon, while lower in wax gourd and cucumber among the four Cucurbitaceae crops. In addition, it had specificity in the expression level of ARF4 in 11 wax gourd germplasms with different fruit sizes, and its expression level in B227 was significantly higher than that in other wax gourd varieties. The expression level of BhARF4 was highest in B227 fruits, particularly those on the day of pollination, followed by leaves, stems and roots. In contrast, the expression level of BhARF4 was lowest in male flower. Subcellular localization analysis showed that BhARF4 protein was located in the nucleus.【Conclusion】The gene structure of BhARF4, the conserved domain of the BhARF4 protein and other biological information characteristics, as well as the gene expression pattern were identified. It is hypothesized that BhARF4 plays a significant role in the growth of wax gourd fruit, particularly during the initial stages of development. And the gene express specifically in different wax gourd materials.